Association between systemic inflammatory indicators on admission and mortality in critically ill patients with diabetic kidney disease based on the MIMIC-IV database: a cohort study - Shen, Guo-Yin; Wang, Qian-Qian; Lv, Si-Ang; Huang, Zhuo-Deng; Zhang, Ru-Lin; Wu, Jun (Frontiers in Endocrinology, 2025)
IntroductionDiabetic kidney disease (DKD) is linked to immunity and inflammation. We aimed to investigate if systemic inflammatory indicators can predict mortality in DKD patients in intensive care units (ICUs) and determine potential associations between them.MethodsThis study included a cohort of 840 adults with DKD in the ICU. Three systemic inflammatory indicators were evaluated by peripheral blood tests: systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), neutrophil-to-lymphocyte ratio (NLR). Cox regression analysis, restricted cubic spline (RCS), and Kaplan-Meier curves were used to evaluate the associations between the inflammatory indicators and the mortality of the DKD population. Receiver operating characteristic (ROC) was employed to ascertain the predictive accuracy of varied systemic inflammatory indicators.ResultsAfter adjusting for all covariates, Cox regression analysis showed that inflammatory indicators were all significantly positively associated with 28-day mortality (SII: HR 1.39, 95% CI, 1.16-1.67, P<0.001; SIRI: HR 1.36, 95% CI, 1.14-1.62, P=0.001; NLR: HR 1.48, 95% CI, 1.20-1.84, P<0.001). Compared with the lowest tertile (tertile 1), participants in the highest tertile (tertile 3) had significantly increased risk of 28-day mortality (SII: HR 2.46, 95% CI, 1.51-4.02, P<0.001; SIRI: HR 3.31, 95% CI, 1.87-5.84, P<0.001; NLR: HR 3.42, 95% CI, 1.94-6.03, P<0.001). Furthermore, ROC curves showed that NLR and SIRI had higher predictive values than SII (NLRAUC vs. SIIAUC: 0.681 vs. 0.633, P=0.006; SIRIAUC vs. SIIAUC: 0.675 vs. 0.633, P=0.041) in predicting 28-day mortality.ConclusionsOur study demonstrated that systemic inflammatory indicators (SII, SIRI, and NLR) were positively associated with 28-day and 365-day mortality in critically ill patients with DKD. Inflammatory indicators may serve as predictors of mortality in critically ill DKD patients.